Contemporary Moroccan Thought : On Philosophy, Theology, Society, and Culture - Hashas, Mohammed, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2025)
Contemporary Moroccan Thought offers a new and broad coverage of the intellectual dynamics and scholarly output of what is presented here as the Rabat School since the 1950s. Geographically situated at the western edge of the classical Arab-Islamic world, Moroccan scholarship has made a belated yet vigorous comeback on the modern Arab intellectual scene, attracting wider reception beyond the Arabic-speaking world, through influential contributions in philosophical, theological, social and cultural studies. This volume sets a new standard in the study of Moroccan, North African, and Middle Eastern societies, and will undoubtedly remain an important scholarly reference for generations to come. Contributors Deina Abdelkader, Nayla Abi Nader, Kholoud Al-Ajarma, Salah Basalamah, Mohamed Wajdi Ben Hammed, Sara Borrillo, Ibrahim Bouhaouliane, Tina Dransfeldt Christensen, Driss El Ghazouani, Brahim El Guabli, Abdennabi El Harri, Amin El-Yousfi, Francesca Forte, Fatma Gargouri, Wael Hallaq, Mohammed Hashas, Alma Rachel Heckman, Aziz Hlaoua, Abdellatif Kidai, Markus Kneer, Mohamed Lamallam, Khalid Lyamlahi, Juan A. Macías-Amoretti, Djelloul Magoura, Mohammed K. B. Rhazzali, Raja Rhouni, Nils Riecken, Fatima Sadiqi, Hamza Salih, Ari Schriber, Simone Sibilio, and Abdessalam Tawil. See Less